(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
Tow samples of Al2O3/CdO mixed oxide were prepared by co-precipitation method at using concentrated ammonia as precipitated agent. The ratio between Al2O3/CdO was .The mixed system was prepared by mixing aluminum chloride solution with cadmium chloride solution and aluminum nitrate solution with cadmium nitrate solution then the samples were named , .Texture properties of the samples were studied and comparison with properties of sample which prepared in previous work. The specific surface area was decreased as following : when were used respectively. The nature of anions affected pore radii anions. The results showed the increasing of micro porosity.